IN SEARCH OF INNOVATION: LOOKING OUTSIDE THE COMPANY - Malachias, Celso dos Santos; Di Serio, Luiz Carlos (Journal of Sustainable Competitive Intelligence, 2017)
In dynamic and highly competitive markets, such as in the Information Technology industry, innovation is imperative for business competitiveness. This research contributes to studies on innovation in the service sector, traditionally known for being less innovative than the manufacturing sector. Through the lens of Absorptive Capacity and Peripheral Vision constructs, this study aims to explore the relationship between innovative capabilities and innovation outcomes, moderated by competitive environment perceived by the companies’ leadership. Utilizing a multiple case study methodology, this paper examines the process of market information acquisition in three small and medium Brazilian Knowledge Intensive Business Service (KIBS) companies. It finds evidence that the Absorptive Capacity and Peripheral Vision have functioned as conditioning factors for more innovative outcomes. Furthermore, it presents indication that the leadership’s perception about the competition in the business environment possibly affects to generate differentiated innovative outcomes.